2015
DOI: 10.1111/jam.12994
|View full text |Cite
|
Sign up to set email alerts
|

Reorganization of Azospirillum brasilense cell membrane is mediated by lipid composition adjustment to maintain optimal fluidity during water deficit

Abstract: This knowledge can be used to develop new Azospirillum brasilense formulations showing an adapted membrane to water deficit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 50 publications
0
13
0
Order By: Relevance
“…Similarly, in the plant Pyrus betuloefolia , the lipid microviscosity of the PM increased in response to PEG while the PM fluidity decreased, indicating an influence of water stress on the physical state of the membrane [59]. In a plant growth-promoting bacterium ( Azospirillum brasilense ), PEG decreased the fluidity a few minutes after treatment, influencing the perception of the water stress by the bacteria and after 1 h, this effect was offset by an adjustment in lipid composition, contributing to the homeostasis of membrane fluidity under water deficit [60]. Similarly, a recent study showed that a NaCl-mediated hyperosmotic stress modified the spatial distribution and abundance of lipid species in roots of barley seedlings [56].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in the plant Pyrus betuloefolia , the lipid microviscosity of the PM increased in response to PEG while the PM fluidity decreased, indicating an influence of water stress on the physical state of the membrane [59]. In a plant growth-promoting bacterium ( Azospirillum brasilense ), PEG decreased the fluidity a few minutes after treatment, influencing the perception of the water stress by the bacteria and after 1 h, this effect was offset by an adjustment in lipid composition, contributing to the homeostasis of membrane fluidity under water deficit [60]. Similarly, a recent study showed that a NaCl-mediated hyperosmotic stress modified the spatial distribution and abundance of lipid species in roots of barley seedlings [56].…”
Section: Discussionmentioning
confidence: 99%
“…Here we show that the previous growth of bacteria with PEG simulating RWC favored both types of motility. This could be related to changes in the composition of the cytoplasmic membrane of bacteria when they grow under a water deficit, demonstrated by the increase of 51% and 21% of phosphatidylcholine in the membrane of Az39 and SEMIA6144 respectively (Cesari et al, 2016;Cesari et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Both cultures were incubated at 28 °C with shaking at 150 rpm (Allied Fisher Scientific) until the stationary phase (24 h for Az39 and 110 h for SEMIA6144) for use in subsequent tests. To simulate a growth restrictive water condition (RWC), the bacterial media were supplemented with 15 mM of non-permeating solute polyethylene glycol (PEG, average MW 5489 Da, Sigma Chemical Co., St. Louis, MO, USA) (Dardanelli et al, 2008;Cesari et al, 2016;Cesari et al, 2018).…”
Section: Plant Materials and Bacterial Strainsmentioning
confidence: 99%
“…Generally, the perturbation of the physical state of the membrane by extrinsic factors initiates an active response that tends to counteract these effects by bringing about intrinsic chemical changes (Cesari et al, ). Although A. guillouiae SFC 500‐1A cells responded by changing mainly the polar head group composition (PtdEtn, Ptd 2 Gro) of membrane PL, the rigidity effect produced by Cr(VI) and Cr(VI) + phenol was promoted rather than counteracted.…”
Section: Discussionmentioning
confidence: 99%
“…The fluidity and order parameters of biological membranes may be modulated by alterations in the polar head groups or acyl chains of phospholipids (PL) (Cesari et al, ; Rowlett et al, ; Smułek et al, ). These changes may be accomplished by varying the total PL amount and/or their class distribution, regulating the fatty acid (FA) unsaturation degree or changing the type of FA incorporated into PL by synthesis or turnover, via phospholipase activity (Cesari et al, ; Markowicz et al, ; Smułek et al, ). In fact, phospholipases are an ubiquitous and heterogeneous group of enzymes that play a critical role in multiple physiological processes and regulate many critical cellular events including membrane homeostasis, nutrient acquisition, signal transduction, and interaction with host cells (Dennis, ).…”
Section: Introductionmentioning
confidence: 99%